It's also about timing! When do pedestrians want to receive navigation instructions. Issue 1 (3rd April 2022) - Golab, Antonia; Kattenbeck, Markus; Sarlas, Georgios; Giannopoulos, Ioannis
ABSTRACT: Despite the increased research interest in wayfinding assistance systems, research on the appropriate point in time or space to automatically present a route instruction remains a desideratum. We address this research gap by reporting on the results of an outdoor, within-subject design wayfinding study ( N = 52 ). Participants walked two different routes for which they requested spoken, landmark-based turn-by-turn route instructions. By means of a survival analysis, we model the points in space at which participants issue such requests, considering personal, environmental, route- and trial-related variables. We reveal different landcover classes (e.g., densely built-up areas) and personal variables (e.g., egocentric orientation and age) to be important, discuss potential reasons for their impact and derive open research questions.